How a Strong Europe Could Create More National Scope of Action - Karl Aiginger (Intereconomics, 2017)
European citizens often assess EU policy as too centralistic and bureaucratic, causing them to vote for populist parties which promise to take “my country back” or even exit from the union. However, many problems – from climate change to the refugee problem – could be better solved at the European level. European policy should try to set rules which enable member countries to address different preferences based on national priorities. Best practices show that this strategy combining centralised policies and decentralised implementation is both feasible and welfare enhancing.
Keywords: 330